Atopic dermatitis : the epidemiology, causes, and prevention of atopic eczema - Williams, Hywel C. (Cambridge University Press, 2000)
Atopic dermatitis or eczema is an increasingly common skin disease, but its distribution, frequency and underlying causes have not yet been systematically reviewed in depth: this is the very first book to look at the epidemiology of atopic eczema, its prevalence and possible causes.